Na Estremadura do Neolítico antigo ao Neolítico final : contributos de um percurso pessoal - Cardoso, João Luís (2016)
The author presents a synthesis of the Neolithic chronological sequence in Estremadura, Portugal. In this region he has developed much of his research, directed archaeological excavations in several important sites and published the results obtained. The nature and characteristics of these sites and their artefacts, along with their absolute chronology, will therefore be the essential elements of this article, without prejudice to its correlation and discussion in a broader framework, based on the information available to other sites with comparative interest.